The effect of pH on the lytic activity of a synthetic mastoparan-like peptide in anionic model membranes - Alvares, Dayane S. [UNESP]; Viegas, Taisa G. [UNESP]; Ruggiero Neto, João [UNESP] (Elsevier, 2018)
Peptide sequences containing acidic and basic residues could potentially have their net charges modulated by bulk pH with a possible influence on their lytic activity in lipid vesicles. The present study reports on a biophysical investigation of these modulatory effects on the synthetic mastoparan-like peptide L1A (IDGLKAIWKKVADLLKNT-NH2). At pH 10.0 L1A was 6 times more efficient in lysing large anionic (1-palmitoyl-oleoyl-sn-glycero-3-phosphocholine (POPC):1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol (POPG)/(8:2)) unilamellar vesicles (LUVs) than at pH 4.0. Despite the reduction of 60% in the L1A net charge in basic pH its affinity for this vesicle was almost insensitive to pH. On the other hand, L1A insertion into monolayers was dramatically influenced by subphase condition, showing that, in the neutral and basic subphases, the peptide induced surface pressure changes that surpassed the membrane lateral pressure, being able to destabilize a bilayer structure. In addition, in the basic subphase, visualization of the compression isotherms of co-spread 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC):POPG (8:2) + 4.8 mol% L1A showed that the peptide induced significant changes in solid lipid domains, indicating its capability in perturbing lipid-packing. An insight into L1A lytic activity was also obtained in giant unilamellar vesicles (GUVs) using phase contrast microscopy. The suppression of L1A lytic activity at acidic pH is in keeping with its lower insertion capability and ability to disturb the lipid monolayer. The lytic activity observed under neutral and basic conditions showed a quick and stochastic leakage following a lag-time. The permeability and the leakage-time averaged over at least 14 single GUVs were dependent on the bulk condition. At basic pH, permeability is higher and quicker than in a neutral medium in good accordance with the lipid-packing perturbation.
Keywords: Peptide-lipid bilayer interaction; pH-dependent lytic activity and lipid-packing perturbation; pH-responsive peptide